The Rationality of the Use of Intravenous Preparations in Diarrhea Patients in the Tk Ii Putri Hijau Kesdam I Bukit Barisan Hospital - D, Darmayanto; W, Wiryanto; Suwarso, Edy (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: to evaluate the rationality of the use of intravenous preparations during diarrhea therapy which is limited to the right patient, the right indication, the right drug and the right dose. Design: the study used descriptive and retrospective design by medical record of the TK II Putri Hijau KESDAM I Bukit Barisan hospital Medan. The criteria taken are patients with diarrhea with bacterial infections in the period of January – December 2018. Interventions: the intervened variable were the rationality of the use of intravenous preparations during diarrhea with bacterial infections. Main outcome measures: the main measurement in this study were the right patient, the right indication, the right drug and the right dose for diarrhea patients with bacterial infections.. Results: there were 885 diarrhea patients included in the inclusion criteria out of a total of 1,302 patients. Inaccurated of drugs used during diarrhea therapy were ceftriaxonee that overdosed in 36 cases and ciprofloxacin that overdosed by 14 cases. Conclusion: it could be concluded that the inaccurate use of ceftriaxonee and ciprofloxacin were included in the incorrect criteria of the right dose for patients with diarrhea with bacterial infections.